The TaCslA12 gene expressed in the wheat grain endosperm synthesizes wheat-like mannan when expressed in yeast and Arabidopsis. (January 2021) - Verhertbruggen, Yves; Bouder, Axelle; Vigouroux, Jacqueline; Alvarado, Camille; Geairon, Audrey; Guillon, Fabienne; Wilkinson, Mark D.; Stritt, Fabian; Pauly, Markus; Lee, Mi Yeon; Mortimer, Jenny C.; Scheller, Henrik V.; et al.
Highlights: Mannan appears early in the developing endosperm of wheat grain. However, the first cell walls of the developing endosperm are devoid of mannan. Mannan related genes were identified in wheat endosperm. TaCslA12 produced pure wheat-like mannan when expressed in yeast and Arabidopsis. Glucomannan were replaced by pure mannan in Arabidopsis stem without visible effect. Abstract: Mannan is a class of cell wall polysaccharides widespread in the plant kingdom. Mannan structure and properties vary according to species and organ. The cell walls of cereal grains have been extensively studied due to their role in cereal processing and to their beneficial effect on human health as dietary fiber. Recently, we showed that mannan in wheat (Triticum aestivum) grain endosperm has a linear structure of β-1, 4-linked mannose residues. The aim of this work was to study the biosynthesis and function of wheat grain mannan. We showed that mannan is deposited in the endosperm early during grain development, and we identified candidate mannan biosynthetic genes expressed in the endosperm. The functional study in wheat was unsuccessful therefore our best candidate genes were expressed in heterologous systems. The endosperm-specific TaCslA12 gene expressed in Pichia pastoris and in an Arabidopsis thaliana mutant depleted in glucomannan led to the production of wheat-like linear mannan lacking glucose residues and with moderate acetylation. Therefore, this gene encodes a mannan synthase and is likely responsible for the synthesis of wheat endosperm mannan.